Strategies Use by Garlic Growers in Coping with Climate Variability in Occidental Mindoro, Philippines - Mary Yole Apple Declaro-Ruedas (Journal of Agricultural Extension, 2020)
The study determined  garlic growerâ€™s perception on livelihoodsâ€™ vulnerability to climate variability, the coping strategies employed, and the relationship between the profile and their coping mechanism to climate variability. Correlational research design was employed in this study.  The respondents were randomly selected from the registered list of garlic growers in the municipalities of San Jose, Magsaysay, Calintaan, Rizal, Looc and Lubang of Occidental Mindoro, Philippines. Survey, interview guide and observation with the garlic growers and farmer leaders were done. Result showed vulnerability to climate variability indicators that were always perceived were pest and disease, lack of water supply and low quality of crops.  The coping strategies that was always practiced was irrigating the land more during dry season using water pumps, since garlic is usually planted in the months of December to April. However, respondents indicated they â€˜neverâ€™ got crop insurance and do not let their land be leased or rented by other farmers. Further, age and farming experience have significant relationship with coping mechanism employed.